Meteorological Factors Influence the Presence of Fungi in the Air; A 14-Month Surveillance Study at an Adult Cystic Fibrosis Center - van Rhijn, Norman; Coleman, James; Collier, Lisa; Moore, Caroline; Richardson, Malcolm D.; Bright-Thomas, Rowland J.; Jones, Andrew M. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Cystic fibrosis is an inherited disease that predisposes to progressive lung damage. Cystic fibrosis patients are particularly prone to developing pulmonary infections. Fungal species are commonly isolated in lower airway samples from patients with cystic fibrosis. Fungal spores are prevalent in the air. Methods We performed environmental air sampling surveillance at the Manchester Adult Cystic Fibrosis Centre, UK (MACFC) over a 14-month period to assess fungal growth inside and outside the CF center. Results Airborne counts of fungal spores peaked from May to October, both in outdoor and indoor samples. Collection of meteorological data allowed us to correlate fungal presence in the air with elevated temperatures and low wind speeds. Additionally, we demonstrated patient rooms containing windows had elevated fungal counts compared to rooms not directly connected to the outdoors. Conclusions This study suggests that airborne Aspergillus fumigatus spores were more abundant during the summer months of the survey period, which appeared to be driven by increased temperatures and lower wind speeds. Indoor counts directly correlated to outdoor A. fumigatus levels and were elevated in patient rooms that were directly connected to the outdoor environment via an openable window designed for ventilation purposes. Further studies are required to determine the clinical implications of these findings for cystic fibrosis patients who are predisposed to Aspergillus related diseases, and in particular whether there is seasonal influence on incidence of Aspergillus related conditions and if screening for such complications such be increased during summer months and precautions intensified for those with a known history of Aspergillus related disease.